TINJAUAN YURIDIS PUTUSAN MAHKAMAH AGUNG TERKAIT PERISTIWA RMS SEBAGAI TINDAKAN MEMINIMALISIR MAKAR DI INDONESIA (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
As a requirement for the crime of treason, the initial element of execution is something that greatly influences whether or not a person can be charged with the crime of treason. A person can be said to have committed the crime of treason and must first be proven regarding the perpetrator's intention as stated at the start of the act, which is one of the elements of attempting to commit the act. criminal. One example occurs in the case of treason in Decision Number No. 1889 K/Pid/2009. Based on the background description, the problems studied are: How is the crime of treason regulated in Indonesia, how is the start of implementation related to the crime of treason, what is the legal analysis of the crime of treason in Decision Number: No. 1889 K/Pid/2009. The research method used in this research is a type of normative legal research, which is supported by secondary data sources, as well as qualitative analysis was carried out. The results of the research were that the regulation of the crime of treason in Indonesia is regulated in several articles, including Article 104, Article 106 of the Criminal Code and Article 107 of the Criminal Code.Sebagai syarat tindak pidana makar, unsur awal eksekusi merupakan hal yang sangat mempengaruhi dapat atau tidaknya seseorang itu didakwa melakukan tindak pidana makar. Seseorang dapat dibuktikan melakukan tindak pidana makar mengenai kesengajaan pelaku sebagaimana dinyatakan pada awal perbuatannya, yang merupakan salah satu unsur percobaan melakukan perbuatan tersebut. pidana. Salah satu contohnya terjadi pada kasus makar pada Putusan Nomor 1889 K/Pid/2009. Berdasarkan uraian latar belakang maka permasalahan yang diteliti adalah: Bagaimanakah pengaturan tindak pidana makar di Indonesia, bagaimana awal mula penerapannya terkait dengan tindak pidana makar, bagaimana analisa hukum terhadap tindak pidana makar pada Putusan Nomor: No. 1889 K/Pid/2009. Metode penelitian yang digunakan dalam penelitian ini adalah jenis penelitian hukum normatif, yang didukung oleh sumber data sekunder, serta dilakukan analisis kualitatif. Hasil penelitian, pengaturan tindak pidana makar di Indonesia diatur dalam beberapa pasal antara lain Pasal 104, Pasal 106 KUHP, dan Pasal 107 KUHP.